2005
DOI: 10.1097/00129492-200503000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mass Loading the Ossicles with a Floating Mass Transducer on Middle Ear Transfer Function

Abstract: The floating mass transducer produces a measurable reduction of the stapes displacement in the temporal bone model. The effect is more prominent at high frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 13 publications
1
58
2
1
Order By: Relevance
“…In contrast to experimental results in temporal bones that predicted only a decrease in middle ear sound transfer at high frequencies [Needham et al, 2005], we also found significant changes at frequencies ≤ 1.5 kHz, indicating that mechanisms other than pure mass load added to the ossicular chain (approx. weight of the FMT = 25 mg) may play a role.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to experimental results in temporal bones that predicted only a decrease in middle ear sound transfer at high frequencies [Needham et al, 2005], we also found significant changes at frequencies ≤ 1.5 kHz, indicating that mechanisms other than pure mass load added to the ossicular chain (approx. weight of the FMT = 25 mg) may play a role.…”
Section: Discussioncontrasting
confidence: 99%
“…4B] in the case of control experiments with their commercially obtained electromechanical transducer [denoted by them as implantable middle-ear hearing device A (IMEHD-A); the manufacturer was not identified, but as explained below it was probably an FMT]. The present results and those of Rosowski et al [2007] are at variance with the results of Needham et al [2005], who report a statistically significant loading effect of the FMT (MED-EL) which systematically increases with frequency and which for the usual incus location amounts to 8 dB at the highest measured frequency of 5 kHz (their fig. 7, position 1).…”
Section: Acoustic Responsescontrasting
confidence: 38%
“…However, they currently provide either limited hearing gain or they may induce an additional hearing impairment [Needham et al, 2005] when the system is inactive. Furthermore, treatment of severe mixed hearing loss is the difficult part.…”
mentioning
confidence: 99%